As inconstâncias políticas no lixão em União dos Palmares -AL - Silva, Claudionor de Oliveira; Silva, Berneval Demezio da; Silva, Izaelma Candido da (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The growth of cities has caused various problems. One of them is the improper disposal of the solid waste, which generates serious impacts to the environment. The purpose of this present paper is to analyze the impacts caused by the garbage dump in União dos Palmares and social issues of collectors. The methodology that has been applied in this study included bibliographical research and field research. The literature based on theoretical studies of Sposito (2010), Jacob (1993), Santos (2009), Carlos (2005) and so on. Two questionnaires were used in the field research: one for the secretary of the Department of Environment, and other for collectors of the garbage dump. It has also drowned up a map of the town’s garbage dump and photographic register of the area of studying. Result indicates that the situation of the garbage dump is worrying. It has noticed that collectors survive in vulnerable situation due to the condition of precarious work, without equipment for protection and garbage handling. All type of garbage is thrown to the ground, causing pollution to the water tables and air pollution, through forest fire. It has still noticed that “RiachoMacaco”/Monkey Stream”, at the edge of the garbage dump, is polluted by diverse wastes and degradation of thereof.